Pengembangan Modul Pembelajaran Berbasis Project Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri 1 Hiliduho - Mendrofa, Versily; Mendrofa, Netti Kariani; Mendrofa, Ratna Natalia; Lase, Sadiana (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
Mathematical problem-solving ability is one of the essential competencies that students must master. However, initial observations at SMP Negeri 1 Hiliduho revealed that students’ problem-solving skills are still relatively low, and Project Based Learning (PjBL)-based teaching materials have not yet been applied in the school. This study aims to develop a PjBL-based instructional module that is valid, practical, and effective in improving students’ mathematical problem-solving ability. The research was conducted using a development approach with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Research instruments consisted of expert validation questionnaires, practicality questionnaires for teachers and students, and a problem-solving test. The data collected were both qualitative and quantitative. Qualitative data were obtained from comments, suggestions, and feedback provided by validators, while quantitative data were derived from the results of validation scores, teacher and student responses, and students’ test results. The research findings showed that the developed learning module was highly valid, as evidenced by validation scores of 98% and 99% from two content experts, 96% from the language expert, and 98% from the design expert. The module was also considered highly practical, with a score of 90.63% from students and 93% from the teacher. Furthermore, the module proved effective in enhancing students’ mathematical problem-solving skills, with an average score of 80.25 (high category) and classical completeness of 83.33% (high category). In conclusion, the PjBL-based module developed in this study fulfilled the criteria of validity, practicality, and effectiveness, thus supporting the achievement of learning objectives.